ALTMAN Z-SCORE ANALYSIS OF FINANCIAL DISTRESS IN ISSI-LISTED COSMETICS AND HOUSEHOLD MANUFACTURING SECTOR - Yuningsih, Firda; Suherman, Usep Deden; Suhendi (Finansha: Journal of Sharia Financial Management, 2025)
This study aims to examine the application of the Altman Z-Score model in assessing financial distress and financial conditions of manufacturing companies in the cosmetics and household needs sub-sectors listed on the Indonesian Sharia Stock Index (ISSI) from 2013 to 2022. Employing a descriptive quantitative approach, the study selects its sample through purposive sampling from the population of relevant manufacturing firms within the ISSI. The findings demonstrate that the Altman Z-Score model effectively analyzes financial distress in these companies. Among the firms studied, PT Akasha Wira Internasional Tbk, PT Mustika Ratu Tbk, PT Unilever Indonesia Tbk, and PT Mandom Indonesia Tbk exhibit healthy financial conditions, whereas PT Martina Berto Tbk shows signs of financial distress. This research provides practical implications for companies by offering a reliable predictive tool to identify potential bankruptcy risks, enabling proactive financial management and strategic decision-making based on current conditions and future prospects.